Development of sequential injection methodologies for the spectrophotometric direct and kinetic determination of aluminium in natural and waste waters - Mesquita, Raquel B. R. (2010)
Two sequential injection methodologies for the spectrophotometric determination of reactive aluminium in water samples are proposed, based on the reaction between chrome azurol S (CAS) and aluminium. The two methods involve a direct and a kinetic methodology (for its application to coloured waste waters), both accommodated within the same manifold. The working ranges obtained were: 0.040-0.500 mg Al Lˉ¹ for direct method and 0.050-0.300 mg Al Lˉ¹ for the kinetic method. The described system has high degree of automation, enabling sampling throughputs of 31 and 57 hˉ¹ for the kinetic method and direct methods, respectively. The reagents consumption per determination is low: 46 μg of CAS, 3.75 mg of sodium acetate and 25 μg of ascorbic acid. The volume of effluent produced per determination is only around 2.8 mL in the direct method and 3.4 mL in the kinetic method.